EP576 A novel multivariable prediction model for lymphatic dissemination in endometrioid endometrial cancer: the lymph node metastasis risk index. (1st November 2019) - Meydanli, MM; Aslan, K; Oz, M; Muftuoglu, KH; Yalcin, I; Engin-Ustun, Y
Abstract : Introduction/Background: The purpose of this study was to develop a risk assessment index that would determine endometrioid endometrial cancer (EC) patients who would benefit from lymphadenectomy. Methodology: Final pathology reports of 353 women who underwent complete surgical staging including pelvic and para-aortic lymphadenectomy for endometrioid EC between January 2008 and June 2018 were retrospectively reviewed. Logistic regression was used to investigate clinicopathological factors associated with positive nodal status. Independent risk factors for lymphatic dissemination were used to build a risk model and 'lymph node metastasis risk index' was defined as '(tumor grade) × (primary tumor diameter) × (percentage of myometrial invasion) × (pre-operative serum CA 125 level)'. The scores used in the 'lymph node metastasis index' were weighted according to the odds ratios assigned for each variable. The lymph node metastasis risk index was calculated for each patient. The diagnostic performance of the model was expressed as sensitivity, specificity, positive predictive value, negative predictive value, positive likelihood ratio and negative likelihood ratio. Results: The 'lymph node metastasis risk index' correctly estimated 35 of 40 lymph node-positive women at a cutoff point of 981.0 (sensitivity 87.5%, specificity 86.3%, negative predictive value 98.2%, positive predictive value 44.9%, positive likelihood ratio 6.37, negative likelihood ratio 0.14). The area under curve of the receiver-operating characteristics was 0.90 (95% Confidence Interval 0.858–0.947) at this cutoff. The clinical accuracy of the model was 86.4%. When a cutoff point of <981.0 was selected in order to define women at low-risk for lymphatic dissemination, our prediction model classified 275 women (77.9%) as being at low-risk for nodal involvement. Among these 275 women, 5 had actually positive lymph nodes; pointing out a 1.8% of false-negative rate. Conclusion: After external validation, the 'lymph node metastasis risk index' may be a valuable tool in the surgical management of endometrioid EC. Disclosure: Nothing to disclose.